Zagraniczna współpraca partnerska i terytorialna na przykładzie pogranicza polsko-niemieckiego - Ładysz, Jerzy (Foreign Partner and Territorial Co-Operation - Case Study of Polish-German Borderland, 2007)
The accession to the European Union gave new impulses to the further development of foreign partner and territorial co-operation in Poland. The most intensive in comparison with the rest of country is the Polish-German co-operation of the local self-governments. At the beginning of 2006 there has been conducted poll research. The aim of the research was to make the diagnosis of partner co-operation realized in the frame of the Euroregion Nysa. Responses to the poll allow to answer such questions as: which Polish cities, gminas and poviats have partners abroad, which events were most important and have to be realized in the future together with the foreign partner, which fields of co-operation are favored, who realizes this co-operation and which sources of financing are used.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (14); 2007; nr 1164, s. 184-194